Socialization of Business and Islamic Accounting: Sosialisasi Bisnis dan Akuntansi Islam - Hidayat Hidayat; Syaefulloh; Zulhelmy (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The reality is that business and accounting practices still contain MaGhRib elements (Maysir, Gharar, and Riba). So that the business practices carried out are contrary to muamalah in Islam. For this reason, socialization was carried out to the people of Teluk Meranti Village about Business and Islamic Accounting. The writing method used is a qualitative approach with a descriptive-explanative model which intends to provide a detailed description of the implementation of Community Service (PkM) activities on Business and Accounting in Islam. From these activities, it is considered very good and useful for the community. Because, from the activities carried out, a lot of knowledge is obtained, such as business and accounting concepts in Islam. People are aware of the mistakes they have made so far. After participating in the socialization, they are committed to making changes, so that the business practices carried out gain profit, blessing and loss